Rural public library network: Rural public libraries development in Malaysia and Australia / Roziya Abu - Abu, Roziya (Universiti Teknologi MARA, Kedah, 2013)
The Malaysian government has invested in public libraries with the intention of promoting development, particularly in rural areas. Despite the increasing number of rural public libraries being built throughout Malaysia, providing users with many services, activities and programs, previous research indicates that they are underutilised. This research aimed to explore relationships between rural public libraries and their communities in both Malaysia and Australia, with particular attention to empowerment and community development processes. This study adopted a multiple case study methodology with a purposive sample of six rural public libraries, three in Malaysia and three in Australia. Qualitative methods were used, including personal interviews, observations of group meetings, group discussions, and document review. The research found that in the Malaysian rural public library services included in this study, activities and programs are standardised and limited mostly to children, taking little account of local community information needs. Participants indicated that the materials and resources are frequently out-dated, and they perceived the library services as being mainly for children. The Australian rural public libraries included in this study facilitate greater community participation and involvement and are more responsive to the needs of local communities, providing support and assistance for lifelong learning and access to information literacy. It is suggested that development activities will have greater impact if local communities are involved and have a sense of ownership of the activities. The study proposes a framework for the development of more responsive rural public library services in developing countries such as Malaysia. Particular strategies are suggested, including locally-focussed collection development, consultation regarding local information needs, the development of local partnerships, and the development of Rural Public Library Networks.